Effects of a sound intervention on physical and emotional well-being in patients with cancer: a prospective randomized trial - Hohneck, Anna; Meissner, Rosa; Hofheinz, Christina; Heinemann, Lara; Christians, Kathrin; Merx, Kirsten; Weingärtner, Simone; Mavratzas, Athanasios; Schulte, Nadine; Burkholder, Iris; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter (Oncology research and treatment, 2023)
Aim: Cancer remains a disease with a significant impact on morbidity and mortality but also on quality of life. This prospective randomized pilot study investigated the effects of a sound intervention on physical and emotional well-being in outpatients with cancer. Methods: Two self-applied sound interventions were used for this purpose, either active “music playing” with a body monochord or passive sound intervention with headphones to listen to a given music compilation. Interventions were carried out over a period of 4 weeks for at least 15 min in the evening before bedtime. The following self-assessment questionnaires were completed both at baseline and after 4 weeks to evaluate the response: the Pittsburgh Sleep Quality Index (PSQI), the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ-C30), Visual Analogue Scale (VAS) for pain and fatigue, and the Fear of Progression (FoP) questionnaire. Primary endpoint of this exploratory trial was to describe the rate of patients with improvement in at least one dimension without worsening of any other. Results: 73 patients (29 male, 44 female) were included in the study and randomized to either active (n = 34, 47%) or passive sound intervention (n = 39, 53%). Median age was 52.0 years (range 21-79). Fourteen patients (19%) stated that they were musically active. The sound intervention was carried out on a median of 26 days (range 5-28). A higher percentage of patients in the passive group reached the primary endpoint: n = 15 (39%) versus n = 9 (27%). Response differences in favour of the passive group were seen with the VAS fatigue and with QLQ-30 questionnaires. Overall, an improvement in QLQ-30 questionnaire was seen in 12 patients (31%) in the passive group versus 3 patients (9%). Moreover, sound intervention significantly improved social functioning and shortness of breath in the passive group according to QLQ-C30. Significant improvements were also noticed in the passive group in terms of affective reactions as a domain of the FoP questionnaire. No effects on pain or sleep quality could be observed. Conclusion: A 4-week self-administered sound intervention was feasible in outpatients suffering from cancer. Using a panel of 5 questionnaires, passive sound interventions appeared to be more likely to positively influence patient-reported outcomes. In particular, a positive impact was documented in social functioning and fatigue.